2000
DOI: 10.4049/jimmunol.165.2.1102
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of CC Chemokines and the CCR5 Receptor in the Pancreas Is Associated with Progression to Type I Diabetes

Abstract: We investigated the biological role of CC chemokines in the Th1-mediated pathogenesis of spontaneous type I diabetes in nonobese diabetic (NOD) mice. Whereas an elevated ratio of macrophage inflammatory protein-1α (MIP-1α):MIP-1β in the pancreas correlated with destructive insulitis and progression to diabetes in NOD mice, a decreased intrapancreatic MIP-1α:MIP-1β ratio was observed in nonobese diabetes-resistant (NOR) mice. IL-4 treatment, which prevents diabetes in NOD mice by polarizing intraislet Th2 respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
107
0
1

Year Published

2002
2002
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(124 citation statements)
references
References 46 publications
13
107
0
1
Order By: Relevance
“…Due to the considerable overlap of measurements at the different time points these cytokine measurements do not qualify as diagnostic markers on an individual basis. However, they may offer insights on the role of chemokines in type 1 diabetes and our findings such as associations with remission or metabolic parameters are in line with observations made in animal experiments in vivo [4,23,24].…”
Section: Discussionsupporting
confidence: 89%
“…Due to the considerable overlap of measurements at the different time points these cytokine measurements do not qualify as diagnostic markers on an individual basis. However, they may offer insights on the role of chemokines in type 1 diabetes and our findings such as associations with remission or metabolic parameters are in line with observations made in animal experiments in vivo [4,23,24].…”
Section: Discussionsupporting
confidence: 89%
“…Cloned human autoreactive T cells express CXCR3, a chemokine receptor associated with T cell infiltration in insulitis The expression of various chemokine receptors associated with type 1 diabetes (CCR5, CXCR3 [19][20][21]), with various sites of inflammation (CCR1, CCR4 and CXCR6) or with homing to T cell zones in lymphoid organs (CCR7 [22], CXCR4 [23]) was analysed on the two islet-specific autoreactive T cell clones (1C6 and PM1#11) as well as on the hsp60-specific T cell clone (Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
“…The contribution of CCR5 to the pathogenesis of autoimmune diabetes in NOD mice was indirectly demonstrated by reduced insulitis and protection from diabetes in NOD. MIP-1α −/− mice, the chemokine that binds to CCR5 [19]. A contribution of CXCR3 as well as CCR4 in autoimmune diabetes or pancreatic infiltration has also been documented [20,40,41].…”
Section: Discussionmentioning
confidence: 98%
“…In NOD mice, g -cell expression of CCL2 (monocyte chemotactic protein-1, MCP-1) leads to insulitis, with a predominance of macrophages but no diabetes [6]. In another study, CCL3 (macrophage inflammatory protein-1 § , MIP-1 § ) -/-NOD mice showed reduced incidence of pre-diabetic symptoms at 10 weeks of age [7]. CCR4-expressing T cells were recently shown to participate in insulitis and diabetes development in NOD mice [8], whereas lack of the CXCR3 chemokine receptor delayed the onset of induced diabetes in a transgenic NOD mouse model [9].…”
Section: Introductionmentioning
confidence: 99%
“…CCR4-expressing T cells were recently shown to participate in insulitis and diabetes development in NOD mice [8], whereas lack of the CXCR3 chemokine receptor delayed the onset of induced diabetes in a transgenic NOD mouse model [9]. down-regulated following IL-4 treatment [7,9]. In the present study, we observed an increase in CCR5-expressing T and B cells in NOD mice, and correlated the expression of this chemokine receptor in T cells with an activated/effector cell phenotype.…”
Section: Introductionmentioning
confidence: 99%